2013
DOI: 10.4300/jgme-d-13-00002.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resident Evaluations of Obstetrics and Gynecology Faculty on Promotion

Abstract: Background Promotion for academic faculty depends on a variety of factors, including their research, publications, national leadership, and quality of their teaching. Objective We sought to determine the importance of resident evaluations of faculty for promotion in obstetrics-gynecology programs. Methods A 28-item questionnaire was developed and distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…While the overall evaluation discrepancy of 0.09 is small, and unlikely to be the sole contributor of a department's decision to promote an individual, teaching quality is becoming increasingly important in promotion decision-making. 22 Furthermore, the differences in clinical teaching evaluations may also contribute to differences in the selection of teaching awards and recognitions within departments. Future studies should examine whether there is a difference in the gender distribution of teaching awards by medical students for clinical physician faculty.…”
Section: Discussionmentioning
confidence: 99%
“…While the overall evaluation discrepancy of 0.09 is small, and unlikely to be the sole contributor of a department's decision to promote an individual, teaching quality is becoming increasingly important in promotion decision-making. 22 Furthermore, the differences in clinical teaching evaluations may also contribute to differences in the selection of teaching awards and recognitions within departments. Future studies should examine whether there is a difference in the gender distribution of teaching awards by medical students for clinical physician faculty.…”
Section: Discussionmentioning
confidence: 99%
“…Curran et al found that positive teaching evaluations could help offset lower publication rates for clinical-track faculty seeking promotion. 31 Additionally, they found that at least one of six departments surveyed had delayed or denied promotion based on poor teaching evaluations.…”
Section: Teachingmentioning
confidence: 99%
“…2 Thus, academic promotion and success can be affected by trainee evaluations. 3 Trainee evaluations have also been used to assess how changes to faculty roles improve clinical education. 4 Therefore, identifying and understanding factors that influence faculty evaluations is important.…”
Section: Introductionmentioning
confidence: 99%